Consolidating Social Protection and Labor Policy in Tunisia : Building Systems, Connecting to Jobs - World Bank Group (World Bank, Washington, DC, 2016)
Tunisia today represents a paradox: despite political progress since its 2011 revolution, wide economic and social disparities persist, threatening stability. While Tunisia has several social protection and labor programs in place, its ability to respond to increasing social needs is compromised by inefficiency, fragmentation, and inequity. The objective of this note is to evaluate the effectiveness of Tunisia’s main social protection and labor programs and identify options for reform through a systems-based approach. The note accompanies the Tunisia systematic country diagnostic (2015) with evidence on the efficiency and equity of key social protection and labor programs. Importantly, this note contributes new analysis on how to bolster Tunisia’s social protection and labor programs by focusing on three main areas of systems building: (i) financing and sustainability, (ii) institutions and governance, and (iii) service delivery. The note argues that without significantly improving institutional coordination on financing and delivery, Tunisia’s social protection and labor system will be ill equipped to strengthen economic and social inclusion.